An Analysis of the Definition of Smart City and its Critical Role in Future-Proofing Projects and Estate Development for the Philippine Construction Industry - Siman, Bennegreg P. (Future Science / FSH-PH Publications, 2025)
Since the concept of smart city came into existence about a decade ago, it certainly has taken a different meaning from basic infra-structure management to integrating advanced technologies in the form of 5G, IoT, and AI. This paper investigates how the definition of smart cities is evolving, its relevance to the Philippine construc-tion industry, estate development, and how it navigates through the challenges and opportunities of integrating it into the society. The research utilized a meta-analysis research design of peer-reviewed journals, government reports, and other articles pub-lished from year 2000 to 2024. The result of the study showed that building or integrating a smart city is beneficial for a country expe-riencing rapid economic development. Nonetheless, the Philip-pines, even if it is considered as one of the fastest-urbanizing countries with visionary and competent infrastructure developers among the countries in Southeast Asia, the nation still faces signif-icant challenges such as outdated land planning, government frag-mentation, and inefficient resource management. The strategic and sufficient education about what a smart city is would lead to a high probability that concerned industries and institutions will find ways to integrate smart city principles in their school com-munities, which will help contribute to training and producing citi-zens who advocate for a country with smart city systems and technologies. This study emphasized the necessity of designing high quality educational initiatives, policy developments, and facil-itating public-private collaborations where it would promote sus-tainable urban development and eventual national growth in the Philippine’s construction industry.